Geology and preliminary study of gold deposit using biogeochemistry in Ulu Sokor, Tanah Merah, Kelantan - Afida Ayub (2019)
Malaysia is one of the country rich with valuable minerals such as gold. The exploration of gold is actively increase however, the method of biogeochemistry study using plants and soils is not widely used in Malaysia. This method is useful to identify potential of gold deposit in addition to prevent destruction to environment. This research is about geology and preliminary study of gold deposit using biogeochemistry in Ulu Sokor, Tanah Merah, Kelantan. The objective of this research is to determine the concentration of pathfinder elements which are Silver (Ag), Manganese (Mn), Copper (Cu), Iron (Fe) and Lead (Pb). Plant and soil samples were taken in 9 different locations respectively in which soil was taken at the same area with plant sample. The selected plant was taken are Melastoma malabathricum, Mimosa pudica, Dactylis glomerate, Rhamnus frangula and Syzygium zeylanicum together with the soil samples nearby the plants. The samples were analyzed using Atomic Absorption Spectrometry (AAS) and X-Ray Fluorescence (XRF). The petrography of rocks was studied accordingly using optical microscope. Based on the result, elements such as Manganese (Mn) and Lead (Pb) in 18AFDS1 are the highest concentration among others with 86.76 ppm and 3.71 ppm respectively. This can be related to its location which is closer to the new developing mine. Meanwhile for 18AFD8(5), copper (Cu) and iron (Fe) concentration also shows the higher concentration among other location, 1.606 ppm and 173.1 ppm respectively due to its location near mining and ex-mining area. As for hyperaccumulator plant, Melastoma malabathricum and Rhamnus frangula can act as hyperaccumulator plants as the value of bioaccumulation factor is more than 1. As a conclusion, the concentration of pathfinder elements in soils and plants can acts as a medium to locate the gold deposition in Sokor, Tanah Merah, Kelantan.